Real‐time organic aerosol chemical speciation in the indoor environment using extractive electrospray ionization mass spectrometry. (14th August 2020) - Brown, Wyatt L.; Day, Douglas A.; Stark, Harald; Pagonis, Demetrios; Krechmer, Jordan E.; Liu, Xiaoxi; Price, Derek J.; Katz, Erin F.; DeCarlo, Peter F.; Masoud, Catherine G.; Wang, Dongyu S.; Hildebrandt Ruiz, Lea; et al.
Abstract: Understanding the sources and composition of organic aerosol (OA) in indoor environments requires rapid measurements, since many emissions and processes have short timescales. However, real‐time molecular‐level OA measurements have not been reported indoors. Here, we present quantitative measurements, at a time resolution of five seconds, of molecular ions corresponding to diverse aerosol‐phase species, by applying extractive electrospray ionization mass spectrometry (EESI‐MS) to indoor air analysis for the first time, as part of the highly instrumented HOMEChem field study. We demonstrate how the complex spectra of EESI‐MS are screened in order to extract chemical information and investigate the possibility of interference from gas‐phase semivolatile species. During experiments that simulated the Thanksgiving US holiday meal preparation, EESI‐MS quantified multiple species, including fatty acids, carbohydrates, siloxanes, and phthalates. Intercomparisons with Aerosol Mass Spectrometer (AMS) and Scanning Mobility Particle Sizer suggest that EESI‐MS quantified a large fraction of OA. Comparisons with FIGAERO‐CIMS shows similar signal levels and good correlation, with a range of 100 for the relative sensitivities. Comparisons with SV‐TAG for phthalates and with SV‐TAG and AMS for total siloxanes also show strong correlation. EESI‐MS observations can be used with gas‐phase measurements to identify co‐emitted gas‐ and aerosol‐phase species, and this is demonstrated using complementary gas‐phase PTR‐MS observations.